Investigation on job involvement, role ambiguity, job demand and work-family conflict: Moderating by social support - Sobanah Dhevi, Tharmalingam (2014)
Past research has pointed out that the employee with the problem of work-family conflict is disadvantageous to the individual and the organization. This is because the work- family conflict in the workplace is considered as disadvantageous, more than a few factors have been recommended to get the better understanding about the reasons why the employees usually easily involved with work-family conflict. There are many predictors to determine the work-family conflict among employees and one of the significant predictor is related to the organization. In spite of, these empirical studies inform that the literature indicate that there are fewer concentration has been focused on the influence of job involvement, role ambiguity, job demand and social support towards the work-family conflict. Thus, the present study fill in the gap by investigating the relationship between job involvement, role ambiguity, job demand, social support and work-family conflict among the administrative staff in University Utara Malaysia (UUM), Kedah which is the public university by use the multiple regression analysis technique. There is two hundred of administrative staff in UUM, whom working in the Malaysian public university were participated in this study. The job involvement and social support show the negative and significant relationship related to the work-family conflict and supported the hypothesis. Then, job demand is significantly and positively related to the work-family conflict and the hypothesis is supported. Next, the role ambiguity is positively related to the workfamily conflict, but not significant and the hypothesis is not supported. Besides that, the social support as a moderator between the job involvements, job demand and role ambiguity towards the work-family conflict is supported and significantly related. The practical implications of the finding have been discussed.